Improving the mastery of raise values using the focus group discussion method: an experimental study of members of the Petra Christian Education and Teaching Association - Lim, Arif Alfan Nour; Winoto, Hery; Andriono, Takim (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This school action research used focus group discussions to increase mastery of RAISE values among Perhimpunan Pendidikan dan Pengajaran Kristen (PPPK) members. The research subjects consisted of 5 members of the PPPK Petra association. This research uses an instrument in the form of the RAISE Values Mastery Questionnaire to determine the level of mastery of RAISE values, then uses a rubric and assessment form to assess mastery of the material when the focus group discussion is conducted. Researchers collected data by providing a checklist as a form of involvement of association members during discussions carried out through focus group discussions. This research uses the method proposed by LeMire et al. (2019) in two cycles. The initial condition is pre-cycle mastery of the RAISE value of 73.71%. The first treatment involves conducting the initial trial or cycle and supplying the association's members with materials, obtaining mastery of the RAISE value of 81.76%, an increase of 8.05%. By providing materials containing focus group talks and questions and answers, the experimental investigation for the second stage was able to acquire 82.50% mastery of the RAISE score. The results of the second stage increased by 8.78% from the pre-cycle stage and 0.74% from the second stage. The treatment given by testing the significance of the differences for the first and second cycles compared to the pre-cycle was found to be significant. There was a substantial difference between the outcomes of the first and second cycles of the various t-tests. The treatment given in the form of an experiment shows that providing materials, focus group discussions, and adequate explanations can increase the mastery of RAISE values among PPPK Petra Surabaya members. The practical contribution of research for practitioners and education managers is to regularly disseminate information about organizational values and provide ongoing training to increase the meaning of the organization's values. Theoretical contribution of research by enriching organizational culture, communication, and human resources development theories.